2012
DOI: 10.1111/j.1532-849x.2012.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Treatment of the Interfacial Surface on Fatigue‐Related Microtensile Bond Strength of Milled Zirconia to Veneering Porcelain

Abstract: Airborne particle abrasion of the interfacial surface of the Everest® Y-TZP core significantly decreased the MTBS to ZirPress veneering porcelain when compared to no interfacial surface treatment. Application of ZirLiner to the interfacial surface of the Everest® Y-TZP core did not significantly increase or decrease the MTBS to ZirPress veneering porcelain, compared to the other surface treatments. Cyclic loading did not affect bond strengths in any of the groups, regardless of surface treatment. Neither cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 25 publications
7
35
0
1
Order By: Relevance
“…Surface treatments have been studied on zirconia to improve bond compatibility between the two ceramics and appear to be important to improving bond strength (13,(15)(16)(17)(18)(19). The present work found that porcelain glaze application on the zirconia core before veneering porcelain cylinder build-up promoted zirconia-porcelain bond improvements, while the untreated group showed the lower bond strength result.…”
Section: Discussionmentioning
confidence: 51%
“…Surface treatments have been studied on zirconia to improve bond compatibility between the two ceramics and appear to be important to improving bond strength (13,(15)(16)(17)(18)(19). The present work found that porcelain glaze application on the zirconia core before veneering porcelain cylinder build-up promoted zirconia-porcelain bond improvements, while the untreated group showed the lower bond strength result.…”
Section: Discussionmentioning
confidence: 51%
“…There is a general agreement among studies that sandblasting of Y-TZP has negative effect on the bond strength of veneering porcelain. 3,24,26,27 This destructive effect has been related to the tetragonal to monoclinic solid phase transformation, induced by the collision of alumina particles during sandblasting. 10,24,26,27 Significantly lower CTE in monoclinic form may induce tensile (rather than compressive) stresses at the surface layer, which causes failure in lower shear stresses.…”
Section: Discussionmentioning
confidence: 99%
“…3,24,26,27 This destructive effect has been related to the tetragonal to monoclinic solid phase transformation, induced by the collision of alumina particles during sandblasting. 10,24,26,27 Significantly lower CTE in monoclinic form may induce tensile (rather than compressive) stresses at the surface layer, which causes failure in lower shear stresses. 25 Wang et al also have mentioned that the toughness of zirconia/veneer interface without any treatment is significantly higher than that of interfaces subjected to airborne-particle abrasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two contradictory types of reports concerning the effect of sandblasting on a zirconia surface: one says that sandblasting improves bond strength 20,21) ; the other says that sandblasting does not affect bond strength 22,23) . The reasons for these contradictory conclusions about sandblasting may to be: (1) different types and sizes of blasting particles or levels of injection pressure could have different effects on the zirconia surface; and (2) sandblasting would change some of the crystals on the zirconia surface from tetragonal to monoclinic 24) .…”
Section: Discussionmentioning
confidence: 99%